Elaborated Peer Assessment of Academic Writing Between Postgraduate Students - Topping, Keith (Autonomy and Responsibility Journal of Educational Sciences, 2024)
Peer assessment in higher education has grown enormously in the last decade, but is more commonly used with undergraduates. In this study, reciprocal paired peer assessment of academic writing was undertaken by twelve postgraduate students of educational psychology, who gave elaborated formative feedback on each other’s work, as did staff. Overall, staff and peer assessments showed a very similar balance between positive and negative statements, but this varied according to assessment criterion. However, only half of the content of detailed formative assessment statements made showed correspondence between staff and peers. Nevertheless, there was very little evidence of conflict between the views of staff and peers - rather, they focused on different details. Subjective feedback from students indicated that most found the process time consuming, intellectually challenging and socially uncomfortable, but effective in improving the quality of their own subsequent written work and developing other transferable skills. The reliability and validity of this type of peer assessment thus appeared adequate, and the partiality of overlap in detail between staff and peer assessments suggested that the triangulation peer assessment offers is likely to add value. However, caution is indicated regarding the generalisation of this finding. Implications for action are outlined.